2014
DOI: 10.1002/elps.201300607
|View full text |Cite
|
Sign up to set email alerts
|

Enantioseparation of new triadimenol antifungal active compounds by electrokinetic chromatography and molecular modeling study of chiral recognition mechanisms

Abstract: Chiral separation of 12 new triadimenol antifungal active compounds by electrokinetic chromatography and chiral recognition mechanisms by computer-aided molecular modeling techniques were studied. Seven neutral cyclodextrins were used as chiral selectors. Heptakis-(2,3,6-tri-O-methyl)-β-cyclodextrin (TM-β-CD) exhibited a very high enantioselectivity power to 12 active compounds compared to the other tested CDs. The influences of the concentration of TM-β-CD, buffer pH, buffer concentration, applied voltage, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…The approaches used in this field are mainly nuclear magnetic resonance (NMR) spectroscopy [9][10][11], molecular modelling [12][13][14], and computer simulations [8]. The combination of chiral CE with molecular modelling and NMR experiments or other supporting techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The approaches used in this field are mainly nuclear magnetic resonance (NMR) spectroscopy [9][10][11], molecular modelling [12][13][14], and computer simulations [8]. The combination of chiral CE with molecular modelling and NMR experiments or other supporting techniques (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Chai and co‐authors reported the enantioseparation of triadimenol antifungal compounds by CEKC with TM‐β‐CD, which showed higher enantiorecognition ability compared to other CDs such as α‐CDs, HP‐α‐CD, hydroxypropy‐β‐CD (HP‐β‐CD), and 2,6‐DM‐β‐CD [182]. In this study, molecular docking was used to visualized the structures of low‐energy guest/TM‐β‐CD complexes and the involved noncovalent interactions.…”
Section: Molecular Modeling Of Capillary Electrophoresis Enantioseparations Promoted By Cyclodextrins: Applicationsmentioning
confidence: 99%
“…In addition, the plurality of CD derivatives across the spaces and substituents meets the possibility of enantiomeric separation for large-scale chiral compounds [152]. CDs act as chiral selectors to separate enantiomers and are suitable for related strategies, such as capillary derivatization, inclusion complex formation mec-hanism, chiral recognition, molecular modeling, quantitative approaches, also detection of analytes [153][154][155][156][157][158][159][160][161][162][163]. 15 different cyclodextrin derivatives were investigated as a chiral complexing reagent.…”
Section: Cyclodextrins and Its Derivatives As Chiral Selectorsmentioning
confidence: 99%